2021
DOI: 10.3233/efi-211560
|View full text |Cite
|
Sign up to set email alerts
|

How can libraries support dementia friendly communities? The study into perceptions and experiences of Croatian public librarians

Abstract: Alzheimer’s Disease (AD), the most common cause of dementia, is an incurable neurological disease with an unknown cause. Since AD is not only social and health challenge but also an economic and fiscal burden and its prevalence is expected to grow exponentially as world population gets older, in 2012 the World Health Organization (WHO) and Alzheimer’s Disease International (ADI) recognized dementia as a global public health priority. Although librarians have not generally been recognized as professionals carin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Moreover, they thought that public libraries can play an important role in developing dementia-friendly communities by improving the quality of life of persons with dementia and their family members, and by contributing to public awareness about dementia and the removal of the social stigma connected to it. Similar results were obtained in a study among Croatian librarians, who did not see themselves as an integral part of the care team for dementia yet believed that public libraries should provide quality services for people with dementia and their family members (Faletar Tanackovic ´et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, they thought that public libraries can play an important role in developing dementia-friendly communities by improving the quality of life of persons with dementia and their family members, and by contributing to public awareness about dementia and the removal of the social stigma connected to it. Similar results were obtained in a study among Croatian librarians, who did not see themselves as an integral part of the care team for dementia yet believed that public libraries should provide quality services for people with dementia and their family members (Faletar Tanackovic ´et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
“…A recent study has shown that 45% of Croatian citizens believe that dementia is a mental illness and part of the normal ageing process (HUAB, 2018). Although librarians worldwide are increasingly serving this vulnerable and growing user group, libraries in Croatia currently do not offer any dementia programmes on a regular basis (Faletar Tanackovic ´et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although majority of respondents believed that people with dementia should have access to appropriate library services, they do not offer any such services yet. Nevertheless, they do provide dementia‐related materials (fiction, non‐fiction) for the general public and CGs, and would welcome partnerships in providing targeted programing for people with dementia (Faletar Tanacković, Petr Balog & Erdelez, 2021). An analysis of online survey among library students at University of Osijek and in‐person interviews with older adults in the local senior citizen social club indicated that their knowledge about dementia is below average.…”
Section: Translation Of Dementia‐related Research Into Practicementioning
confidence: 99%
“…Although librarians have not been traditionally regarded as professionals who support people with dementia, recent inclusion of a person‐centred and evidence‐based community (neuro)rehabilitation into the dementia care and wider acceptance of social model of disability (which argues that a person is not impaired by their condition but by social, economic, attitudinal, physical and other barriers in the society), has motivated library and information science scholars to join the efforts of healthcare and social care professionals and investigate how they can support people living with dementia and contribute to the development of dementia‐friendly communities as a part of their inclusion, diversity and social justice agenda (Erdelez, Howarth & Gibson, 2015; Riedner, 2020; Dickey, 2020; Dai, Bartlett & Moffatt, 2021; Faletar Tanacković, Petr Balog & Erdelez, 2021). McNicol (2023) states that libraries, just as a society as a whole, must change the way they think about people with dementia and try to understand how they can better serve them through customer service, resources, reading interventions, design and development of more positive and inclusive attitudes toward people with dementia among library staff.…”
Section: Introductionmentioning
confidence: 99%